Empowering Children Through Digital Marketing: A Social Reintegration Strategy for Children in Conflict with The Law - Belgis Hayyinatun Nufus; Budhy Santoso; Atik Rahmawati; Maisaroh Choirotunnisa; Ria Faisyahril (Ali Institute of Research and Publication, 2026)
Children Facing the Law (ABH) often experience social stigma and limited access to economic opportunities, thus requiring measurable social reintegration strategies. This community service program was conducted at Nurul Huda Islamic Boarding School, focusing on empowerment through digital marketing skills, particularly in the culinary and garment sectors. The objective of this activity was to enhance participants’ capacity to utilize digital marketing as a means of adaptation and social reintegration. The method employed was participatory training based on hands-on practice, including content planning sessions, simulations of e-commerce platform usage, and assistance in online product marketing. The results indicate an increase in participants’ digital marketing skills by more than 75%, as measured through pre-test and post-test assessments. Additionally, one e-commerce platform was established to market culinary and garment products, and an increase in entrepreneurial motivation was observed, as indicated by 100% of participants through simple direct expressions. These findings suggest that practice-based training with an empowerment approach can serve as an effective strategy in supporting the social reintegration of ABH.